1992
DOI: 10.1111/j.1460-9568.1992.tb00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ciliary Neurotrophic Factor and the Neurotrophins – Nerve Growth Factor, Brain‐Derived Neurotrophic Factor and Neurotrophin 3—in Cultured Rat Hippocampal Astrocytes

Abstract: Cultured astrocytes are known to possess a range of neurotrophic activities in culture. In order to examine which factors may be responsible for these activities, we have examined the expression of the genes for four known neurotrophic factors-ciliary neurotrophic factor (CNTF), nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF) and neurotrophin 3 (NT3)-in purified astrocyte cultures derived from neonatal rat hippocampus. Hippocampal astrocytes were found to express mRNA for three neurotrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(118 citation statements)
references
References 67 publications
6
111
1
Order By: Relevance
“…4,6 Astrocytes are located close to the neural stem cells in the adult dentate gyrus 54 and can express several factors that are able to independently increase proliferation. 55,56 Of particular relevance to the present study is the clear connection found between astrocytes, learning and PKCg. 57 Thus, this suggests the mechanism for behavioral reversal, given the well-known connection between PKCg and Morris maze performance.…”
Section: Discussionmentioning
confidence: 58%
“…4,6 Astrocytes are located close to the neural stem cells in the adult dentate gyrus 54 and can express several factors that are able to independently increase proliferation. 55,56 Of particular relevance to the present study is the clear connection found between astrocytes, learning and PKCg. 57 Thus, this suggests the mechanism for behavioral reversal, given the well-known connection between PKCg and Morris maze performance.…”
Section: Discussionmentioning
confidence: 58%
“…The chemokines secreted by MSCs may have acted directly on the NSCs. However, it is also possible that factors secreted by the MSCs activated nearby astrocytes and activation of the astrocytes produced the increase in neurogenesis, because astrocytes are located in close proximity to NSCs (6) in the hippocampus and express several factors that independently increase neurogenesis (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported that primary astrocytes in culture produce NGF, BDNF and NT 3 , and that the expression of these neurotrophins and their receptors in astrocytes is modulated by cAMP signaling (Furukawa et al, 1987;Houlgatte et al, 1989;Rudge et al, 1992;Condorelli et al, 1994). Thus, astrocytes might release neurotrophins that affect neurons that, in turn, enhance synapse formation and function.…”
Section: Neurotrophin Signaling At Tripartite Synapsesmentioning
confidence: 99%